1987
DOI: 10.1002/ijc.2910400604
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking, occupational exposure and bladder cancer in Argentina

Abstract: The highest rate for bladder cancer in Latin America has been reported from La Plata, Argentina. A case-control study was carried out to investigate the reasons for this high rate. A total of 117 cases, 117 hospital controls and 117 neighbourhood sex- and age-matched controls were interviewed regarding their smoking and drinking habits and occupational exposures. Cigarette smoking and coffee drinking were identified as the major risk factors, and a significant association was also found for truck and railway d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 21 publications
(21 reference statements)
1
36
0
Order By: Relevance
“…11). On the other hand, several older studies have not found statistically significant increases in risk associated with familial history of cancer (7,9,(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 93%
“…11). On the other hand, several older studies have not found statistically significant increases in risk associated with familial history of cancer (7,9,(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 93%
“…Most previous studies reported either null associations 2,6,[17][18][19][20][21][22][23][24] or slightly positive associations 4,5,[25][26][27][28][29] between consumption of alcoholic beverages and risk of bladder cancer. Our results regarding beverage-specific consumption are in agreement with some, but not all, previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the new age-and smoking-adjusted summary odds ratio was 1.35 (95 percent CI: 0.96, 1.91). Associations between specific alcoholic beverages and bladder cancer risk were reported in nine studies without consistent results (12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%